2020
DOI: 10.1016/j.btre.2020.e00563
|View full text |Cite
|
Sign up to set email alerts
|

An overview of anoxygenic phototrophic bacteria and their applications in environmental biotechnology for sustainable Resource recovery

Abstract: Highlights APB are phylogenetically and metabolically diverse, includes many extremophiles. Ability to harvest IR light and use of many inorganic electron donors useful. Electricity, polymers, fertilizers, feed, antioxidants and pigments recoverable. Purple non-sulfur bacteria well studied, have wide range of applications. Metabolic engineering key to improving productivity and metabolic traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 242 publications
0
42
0
3
Order By: Relevance
“…Likewise, these models can also be implemented in crop plants by exploiting conventional molecular biology tools as well as new genomeediting techniques. Besides crop plants, all our results are readily transferable to the highly conserved photorespiratory and photosynthetic cycles found in algae (Alami et al, 2021;Matula and Nabity, 2021), and blue-green algae (George et al, 2020). As algae and fast-growing land plants such as bamboo grass (Devi and Singh, 2021) are fast CO 2 harvesters even without engineering, they are often aimed for potential CO 2 -sequestration applications.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 56%
“…Likewise, these models can also be implemented in crop plants by exploiting conventional molecular biology tools as well as new genomeediting techniques. Besides crop plants, all our results are readily transferable to the highly conserved photorespiratory and photosynthetic cycles found in algae (Alami et al, 2021;Matula and Nabity, 2021), and blue-green algae (George et al, 2020). As algae and fast-growing land plants such as bamboo grass (Devi and Singh, 2021) are fast CO 2 harvesters even without engineering, they are often aimed for potential CO 2 -sequestration applications.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 56%
“…We evidenced that the investigated bottom sediments from Cardinal Pond were characterized by the highest relative abundance of bacteria capable of using CoQ10 pathways. George, et al [ 49 ] indicated that most Gram-negative facultative anaerobes use CoQ10 pathways, and these pathways can be identified in some anoxygenic phototrophic bacteria (isolated from lake sediment). Additionally, the presence of Gram-negative facultative anaerobes may correlate with temporary flooding and drying of the pond [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…George, et al [ 49 ] indicated that most Gram-negative facultative anaerobes use CoQ10 pathways, and these pathways can be identified in some anoxygenic phototrophic bacteria (isolated from lake sediment). Additionally, the presence of Gram-negative facultative anaerobes may correlate with temporary flooding and drying of the pond [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the bacteria, photosynthetic bacteria can synthesize various red, pink, or yellow‐orange carotenoids with unique structure (George et al, 2020). There are many successful examples of photosynthetic bacteria used for carotenoids production.…”
Section: Introductionmentioning
confidence: 99%